2008
DOI: 10.1109/tns.2008.2006753
|View full text |Cite
|
Sign up to set email alerts
|

A Fieldable-Prototype, Large-Area, Gamma-Ray Imager for Orphan Source Search

Abstract: We have constructed a unique instrument for use in the search for orphan sources. The system uses gamma-ray imaging to "see through" the natural background variations that effectively limit the sensitivity of current devices. The imager is mounted in a 4.9-m-long trailer and can be towed by a large personal vehicle. Source locations are determined both in range and along the direction of travel as the vehicle moves. A fully inertial platform coupled to a global positioning system receiver is used to map the ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In another, but more elaborate solution, [26] combined a detector array of gamma imagers [34] with stereo cameras to demonstrate a portal-less highway radiation monitoring system. The classical radiation portal monitors are associated with several limitations amongst which are included: interference with the flow of traffic as vehicles need to slow down at the portals; ease of evasion by smugglers because the portal location is always fixed; and susceptibility to background variation caused by shielding of the detectors as vehicles pass in front of them [26].…”
Section: Integration Of Radiological and Contextual Sensorsmentioning
confidence: 99%
“…In another, but more elaborate solution, [26] combined a detector array of gamma imagers [34] with stereo cameras to demonstrate a portal-less highway radiation monitoring system. The classical radiation portal monitors are associated with several limitations amongst which are included: interference with the flow of traffic as vehicles need to slow down at the portals; ease of evasion by smugglers because the portal location is always fixed; and susceptibility to background variation caused by shielding of the detectors as vehicles pass in front of them [26].…”
Section: Integration Of Radiological and Contextual Sensorsmentioning
confidence: 99%
“…In terrestrial searches for illicit radioactive materials, it has been shown that the use of radiation imaging can increase sensitivity by removing systematic background variations and reducing source confusion issues [3][4][5][6][7]. While radiation background levels are generally lower and less variable in maritime settings, they are still an issue in coastal waters, where many small ship-to-ship inspections occur.…”
Section: Introductionmentioning
confidence: 99%